Analisis Pelanggaran Kesantunan Berbahasa pada Tuturan Transaksi Jual Beli di Pasar Tradisional Kehewanan Samarinda - M. Alief Ramadhany; Widyatmike Gede Mulawarman; Syamsul Rijal (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
In the interactions carried out by traders and buyers in buying and selling transactions in the Kehewanan Traditional Market of Samarinda, some speeches violate the principle of politeness in language. It has prompted researchers to analyze language politeness in the Kehewanan Traditional Market of Samarinda. This study uses a qualitative method. This study's data collection techniques are tapping techniques, listening techniques, recording techniques, and note-taking techniques. The data in this study are the utterances of traders and buyers at the Kehewanan Traditional Market of Samarinda, which violate the politeness principle and the politeness scale proposed by Leech. The results of the study are as follows. First, the scale of politeness of language politeness in buying and selling transactions at the Kehewanan Traditional Market of Samarinda includes cost-benefit, optionality, and indirectness scales. Second, there were also violations of Leech's six politeness maxims, consisting of the maxim of wisdom, the maxim of generosity, the maxim of acceptance, the maxim of humility, the maxim of agreement, and the maxim of sympathy.